Superiority of focused ion beam‐scanning electron microscope tomography of cardiomyocytes over standard 2D analyses highlighted by unmasking mitochondrial heterogeneity. Issue 4 (13th June 2021) - Heinen‐Weiler, Jacqueline; Hasenberg, Mike; Heisler, Martin; Settelmeier, Stephan; Beerlage, Anna‐Lena; Doepper, Hannah; Walkenfort, Bernd; Odersky, Andrea; Luedike, Peter; Winterhager, Elke; Rassaf, Tienush; Hendgen‐Cotta, Ulrike B.
Abstract: Background: Cardioprotection by preventing or repairing mitochondrial damage is an unmet therapeutic need. To understand the role of cardiomyocyte mitochondria in physiopathology, the reliable characterization of the mitochondrial morphology and compartment is pivotal. Previous studies mostly relied on two‐dimensional (2D) routine transmission electron microscopy (TEM), thereby neglecting the real three‐dimensional (3D) mitochondrial organization. This study aimed to determine whether classical 2D TEM analysis of the cardiomyocyte ultrastructure is sufficient to comprehensively describe the mitochondrial compartment and to reflect mitochondrial number, size, dispersion, distribution, and morphology. Methods: Spatial distribution of the complex mitochondrial network and morphology, number, and size heterogeneity of cardiac mitochondria in isolated adult mouse cardiomyocytes and adult wild‐type left ventricular tissues (C57BL/6) were assessed using a comparative 3D imaging system based on focused ion beam‐scanning electron microscopy (FIB‐SEM) nanotomography. For comparison of 2D vs. 3D data sets, analytical strategies and mathematical comparative approaches were performed. To confirm the value of 3D data for mitochondrial changes, we compared the obtained values for number, coverage area, size heterogeneity, and complexity of wild‐type cardiomyocyte mitochondria with data sets from mice lacking the cytosolic and mitochondrial protein BNIP3 (BCL‐2/adenovirus E1B 19‐kDa interacting protein 3; Bnip3 −/− ) using FIB‐SEM. Mitochondrial respiration was assessed on isolated mitochondria using the Seahorse XF analyser. A cardiac biopsy was obtained from a male patient (48 years) suffering from myocarditis. Results: The FIB‐SEM nanotomographic analysis revealed that no linear relationship exists for mitochondrial number ( r = 0.02; P = 0.9511), dispersion ( r = −0.03; P = 0.9188), and shape (roundness: r = 0.15, P = 0.6397; elongation: r = −0.09, P = 0.7804) between 3D and 2D results. Cumulative frequency distribution analysis showed a diverse abundance of mitochondria with different sizes in 3D and 2D. Qualitatively, 2D data could not reflect mitochondrial distribution and dynamics existing in 3D tissue. 3D analyses enabled the discovery that BNIP3 deletion resulted in more smaller, less complex cardiomyocyte mitochondria (number: P < 0.01; heterogeneity: C.V. wild‐type 89% vs. Bnip3 −/− 68%; complexity: P < 0.001) forming large myofibril‐distorting clusters, as seen in human myocarditis with disturbed mitochondrial dynamics. Bnip3 −/− mice also show a higher respiration rate ( P < 0.01). Conclusions: Here, we demonstrate the need of 3D analyses for the characterization of mitochondrial features in cardiac tissue samples. Hence, we observed that BNIP3 deletion physiologically acts as a molecular brake on mitochondrial number, suggesting a role in mitochondrial fusion/fission processes and thereby regulating the homeostasis of cardiac bioenergetics.